2008
DOI: 10.2113/gseegeosci.14.2.81
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Geomorphic Characteristics of Landslides at Coyote Mountain, Anza-Borrego Desert State Park, California

Abstract: Coyote Mountain is an 8-mi-long (13 km) elongate fault block made up of granitic and metamorphic rocks in northeastern San Diego County, California. A series of landslides, most of which have distinct morphology and failure mechanisms, occurs in the tonalite and gneiss underlying the steep southwest slope of the mountain. The southernmost landslide area is the Peg Leg Smith landslide complex, which is composed of several translational slides and a unique remnant of a long-runout rock avalanche. In the central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Because the rock exposed in the canyons flanking the west side of the ridge is highly fractured and lowangle faults that could form a basal rupture surface are not evident or suspected, Hart (2008) suggested that failure occurs along interconnecting fracture systems in step-like fashion because of high transient shear stresses produced during earthquakes along the Coyote Creek and San Jacinto Faults. This ongoing process ultimately results in catastrophic slope failure.…”
Section: Coyote Ridge San Diego County Californiamentioning
confidence: 99%
“…Because the rock exposed in the canyons flanking the west side of the ridge is highly fractured and lowangle faults that could form a basal rupture surface are not evident or suspected, Hart (2008) suggested that failure occurs along interconnecting fracture systems in step-like fashion because of high transient shear stresses produced during earthquakes along the Coyote Creek and San Jacinto Faults. This ongoing process ultimately results in catastrophic slope failure.…”
Section: Coyote Ridge San Diego County Californiamentioning
confidence: 99%